Treatment of autochthonous acute hepatitis E with short‐term ribavirin: a multicenter retrospective study. (30th December 2015) - Péron, Jean Marie; Abravanel, Florence; Guillaume, Maeva; Gérolami, René; Nana, Jean; Anty, Rodolphe; Pariente, Alexandre; Renou, Christophe; Bureau, Christophe; Robic, Marie‐Angèle; Alric, Laurent; Vinel, Jean pierre; et al.
Abstract: Background & Aims: Hepatitis E virus (HEV) genotypes 3 and 4 cause sporadic cases of infection in developed countries. Being elderly and having an underlying liver disease are the main risk factors for death in this population. Chronic infection has been described in immunocompromised patients. Ribavirin is now the antiviral treatment of choice in solid‐organ‐transplant recipients with chronic HEV infection. We hypothesized that early short‐term treatment of acute HEV infection may be useful for patients with risk factors or undergoing chemotherapy. Methods: Between July 2010 and January 2014, 21 patients diagnosed with acute HEV infection were treated with ribavirin, at 600–800 mg/day for up to 3 months. All serum samples were positive for HEV RNA. Results: Nine patients were treated for severe hepatitis. Six patients were aged >70 years. Four patients were receiving an immunosuppressive therapy for an autoimmune disease and two patients were undergoing chemotherapy for a malignancy. Two patients received a fixed‐dose regimen. For all other patients, ribavirin was stopped when HEV became undetectable in the serum. The median duration of ribavirin treatment was 26 days. Two patients developed severe anaemia. Two patients with encephalopathy died. One patient relapsed transiently. All patients were cleared of HEV and regained normalized liver‐enzyme levels. Immunosuppressive treatment and chemotherapy could be resumed. Conclusions: Treatment of acute HEV infection using ribavirin seems safe and effective. Short‐term treatment tailored to viraemia may be the best regimen for this indication.